Mutation of Serine protease 1 Induces Male Sterility in Bombyx mori - Xu, Xia; Wang, Yaohui; Chen, Jine; Du, Xin; Yao, Lusong; Xu, Jun; Zhang, Yong; Huang, Yongping; Wang, Yongqiang (Frontiers in Physiology, 2022)
Serine proteases are important in reproduction, embryonic development, cell differentiation, apoptosis, and immunity. The genes encoding some serine proteases are essential for male fertility in both humans and rodents and are functionally conserved among metazoan. For example, the Serine protease 1 (Ser1) gene determines male reproductive success in the model lepidopteran insect Bombyx mori. In this study, we explored the function of BmSer1 through transgenic CRISPR/Cas9 technology-mediated mutations in silkworm. We found that the mutation of BmSer1 gene resulted in male sterility but had no effect on female fertility. Male mutants produce normal eupyrene sperm bundles, but the sperm bundles do not dissociate into single sperm. Male sterility caused by the BmSer1 gene mutation was inherited stably through female individuals. Therefore, the serine protease encoded by BmSer1 is essential for male reproductive success in lepidopterans and is a potential target gene for biological reproductive regulation.